White mist dog [large type] - Gear, W. Michael (Gear, W. Michael. Saga of the Mountain Sage, 2023)
"Beaten and humiliated, young Richard Hamilton is dropped, bound and filthy, onto the deck of Dave Green's boat, the Maria. In no time, he's looking into the barrel of Green's pistol as the trader contemplates shooting the worthless philosopher as a means of motivating his men. Captured by Packrat, Heals Like A Willow dreams of the White Mist Dog and fights a battle of wits with the Pawnee as he transports her eastward in search of his father. Meanwhile, Richard begins to discover something inside himself, but he's still dedicated to escaping the Maria and making his way back to Boston. All of which comes to a head when he and Travis run headlong into Willow and Packrat. For both Willow and Richard, Maria's hard ascent up the Missouri becomes a journey of discovery; but danger lurks on all sides as scheming boatmen, desperate Native chiefs, and passions of the heart all conspire to destroy them. In the end, Willow will make a choice that will change her and Richard's lives forever"--